Efficient and Sustainable Management of Product Durability and Recyclability - Thomas Eichner; Marco Runkel (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2000)
In a dynamic general equilibrium model we explictly consider the relationship between the product attributes 'durability' and 'recyclability'. Both efficiency and sustainability aspects are taken into account. It turns out (a) that durability may be inefficient even in a perfectly competitive economy in which environmental externalities are absent, (b) that in case where markets for product design are absent the efficiency restoring tax-subsidy schemes may significantly differ from the sustainability restoring tax-subsidy schemes and (c) that changing the property rights for consumption goods and consumption residuals is a promising policy option to overcome market failure.
Keywords: H21; Q28; 330; Umweltökonomik; Öko-Produkt; Kreislaufwirtschaft; Dauerhaftes Konsumgut; Produktlebenszyklus; Allokationseffizienz; Marktmechanismus; Theorie